A forward body-biased low-leakage SRAM cache device, circuit and architecture considerations. - Kim, C.H (IEEE Transactions on VLSI systems)
This paper presents a forward body-biasing (FBB) technique for active and standby leakage power reduction in cache memories. Unlike previous low-leakage SRAM approaches, we include device level optimization into the design. We utilize super high Vt (threshold voltage) devices to suppress the cache leakage power, while dynamically FBB only the selected SRAM cells for fast operation. In order to build a super high Vt device, the two-dimensional (2-D) halo doping profile was optimized considering various nanoscale leakage mechanisms. The transition latency and energy overhead associated with FBB was minimized by waking up the SRAM cells ahead of the access and exploiting the general cache access pattern. The combined device-circuit-architecture level techniques offer 64% total leakage reduction and 7.3% improvement in bit line delay compared to a previous state-of-the-art low-leakage SRAM technique. Static noise margin of the proposed SRAM cell is comparable to conventional SRAM cells.